Primary membranous nephropathy in adolescence: A prospective study. Issue 9 (9th August 2017) - Kumar, Vinod; Varma, Ashwani Kumar; Nada, Ritambhra; Ghosh, Ratan; Suri, Deepti; Gupta, Anju; Kumar, Vivek; Rathi, Manish; Kohli, Harbir; Jha, Vivekanand; Gupta, Krishan; Ramachandran, Raja
Abstract: Aim: Primary membranous nephropathy (PMN) accounts for only 1–2% of nephrotic syndrome in children. Antibodies to m‐type phospholipase A2 receptor (aPLA2 R) is seen in 70% of adult PMN cases. The present study was undertaken to study m‐type phospholipase A2 receptor (PLA2 R) status and clinical behavior in adolescent PMN cases. Methods: The present prospective observational study included adolescent (10–19 years) onset biopsy proved PMN. Patients were followed on a monthly basis with urine protein, serum albumin and creatinine. Serum aPLA2 R was done at baseline and at 6 and 12 months of starting treatment. Patients were treated as per unit's protocol. Results: During the study period a total of 18 patients were enrolled. The mean age of the cases was 16.27 ± 2.39 (11–19) years. Seventeen (94.44%) patients presented with nephrotic syndrome. The mean proteinuria and serum albumin was 4.52 ± 1.93 (2.43–9.20) g/day and 2.1 ± 0.6 (1.1–3.4) g/dL respectively. PMN was PLA2 R related in 83%. aPLA2R and enhanced staining for PLA2 R in glomeruli was seen in 14 (77.78%) and 13 (72.22%), respectively. Clinical remission at the end of 6 and 12 months of therapy was seen in 11 (61.11%) and 9 (50%) subjects respectively. There was a significant association of aPLA2 R to clinical remission/ resistance. Conclusion: Primary membranous nephropathy in adolescent population is aPLA2 R related in over three‐quarters of the cases and the response to therapy is seen in only half of them. aPLA2 R monitoring is clinically relevant and should be incorporated in the management of adolescent onset PMN. Summary: In the present prospective observational study of adolescent onset PMN, we observed PLA2 R related disease in 83% of the subjects. Antibodies and enhanced staining in the glomeruli was seen in 78 and 72% of the patients, respectively. At 6 and 12 months of therapy, 61 and 50% achieved clinical remission respectively and there was a very good association of aPLA2R to clinical activity.